Toward a Transformative Circular Pedagogy Model: Teacher Agency and Sustainability Education in Rural Island Schools - Marlina Deli; Nasir Nasir; Lilianti Lilianti (Sakura Digital Nusantara, 2026)
Background: Sustainability education in marginalized rural–island contexts remains insufficiently theorized, particularly where material scarcity and weak institutional support constrain pedagogical practice. Existing Education for Sustainable Development (ESD) literature predominantly reflects well-resourced settings, offering limited insight into how locally available materials, such as school waste, can be reconfigured as meaningful learning resources. Purpose: This study examines how teacher agency mediates the transformation of school waste into sustainability-oriented learning and develops a context-sensitive model of Transformative Circular Pedagogy. Method: A qualitative multiple-case study was conducted in two public senior high schools in Wakatobi, Indonesia. Data were generated through semi-structured interviews, classroom observations, and document analysis, and analyzed using reflexive thematic analysis supported by NVivo to identify cross-case patterns and construct an integrative model. Findings: The analysis reveals four interrelated processes: (1) waste as epistemic resource, (2) teacher agency as pedagogical driver, (3) experiential learning and student transformation, and (4) institutional fragility and innovation limits. These processes operate within a recursive system in which institutional dynamics continuously reshape material conditions, generating new cycles of pedagogical innovation. Conclusion: This study advances a Transformative Circular Pedagogy Model that reconceptualizes waste as an epistemic catalyst and positions teacher agency as the core mechanism of sustainability learning in resource-constrained contexts. Theoretically, it integrates material, pedagogical, and institutional dimensions into a dynamic circular framework. Practically and at the policy level, the findings highlight the urgency of institutionalizing sustainability education through governance alignment, professional support, and resource provision to ensure long-term scalability and impact.